(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2021)
The motif of this study was to determine the effect of economic sectors on employment in Sub-Saharan Africa, given that the Sub-Saharan African region had had about two decades of sustained economic growth. Thirty Sub-Saharan African countries were used in this study, their data that was obtained and used spanning from the year 1990 to the year 2015. The study made use of the traditional neo-classical aggregate production function in the estimation of the regression results. The software program that was used in data analysis was STATA. Hausman test was undertaken and it determined that fixed effects estimations were preferred to random effect and as a result fixed effects were utilized in the study in carrying out regression analysis. On effect of economic sectors on employment, foreign direct investment was found to negatively influence employment though the influence was not statistically significant. The export and agriculture variables negatively and statistically significantly influenced employment. All the other variables in the study were found to positively and statistically significantly influence employment. Empirical results established that the gender gap in employment was maintained in the whole period of the study with more men being employed than women.